Adaptação da produção aos objetivos de competitividade e produtividade: a pesquisa-ação em uma manufatureira de cutelaria inserida em rede - Kyrillos, Sérgio Luiz; Sacomano, José Benedito; Milreu, Francisco José Santos; Fusco, José Paulo Alves [UNESP]; Souza, José Barrozo de (My University, 2011)
One of the oldest segments in operations management, whose models are always subject to development efforts, for academics and productive organizations, is the management of production and work organization. Proposals for strategic management principles that seek to bring production to streamline processes reduce costs and add value, identifying problems with material flow and information while reducing the response time. This is realized through the pursuit of the best actions to achieve goals and targets established in a successful Planning and Production Control. This article aims to identify and implement actions that increase the speed of supply of goods produced in a enterprise cutlery; positively influencing the perception of customers. Such attitudes benefit all actors involved in the network, a fact which is expressed in the production chain. To lay the foundations of research and validate the data obtained, it was a study drawing on action research methodology. The goods produced are sold, mainly to wholesalers. Was proved seven aspects to improve and enhance the competitiveness of the organization, among them the complete design of the network, integrating upstream and downstream actors.

Um dos segmentos mais antigos da gestão de operações, cujos modelos sempre são submetidos aos esforços de desenvolvimento, por acadêmicos e organizações produtivas, é a administração da produção e a organização do trabalho. As propostas de gestão estratégica da produção trazem princípios que buscam agilizar processos, reduzir custos e agregar valores, identificar problemas de fluxo de materiais e informações além da redução do tempo de resposta. Isso se efetiva por meio da busca das melhores ações para alcançar objetivos e metas estabelecidos num bem sucedido Planejamento e Controle da Produção. Esse artigo busca contribuir, identificar e implantar ações capazes de aumentar a rapidez do fornecimento dos bens produzidos em uma cutelaria; influenciando de maneira positiva a percepção da clientela. Tais atitudes beneficiam todos os atores envolvidos na rede, fato que se expressa na cadeia produtiva. Para lançar as bases da pesquisa e validar dados obtidos, fez-se um estudo valendo-se da metodologia pesquisa-ação. Os bens produzidos são vendidos, preferencialmente, para atacadistas - por dominarem a distribuição - embora imponham exigências relativas a preços, prazos, pagamento. Comprovaram-se sete aspectos relevantes para melhorar e aumentar a competitividade da organização; entre estes a visão completa da rede, integrando atores a montante e a jusante.
Adaptation of production to the objectives of competitiveness and productivity: action research in a manufacturing cutlery inserted into the network
Keywords: Business networking; Planning and production control; Management systems operations; Empresas em rede; Planejamento e controle da produção; Gestão; Sistemas de operações